Significance Of Cervical Cytology Screening (Pap Smear) In The Detection Of Precancerous Cervical Lesions
Summary: Background: The incidence of cancer of the cervix is comparatively low in Iraq, as in most other Islamic countries. Pre invasive lesions of the uterine cervix can be detected by Pap smears in their preclinical course, a fact which documents the significant role of cervical cytology in gynecological practice. Objective: To emphasize the role of cervical cytopathology (Pap smears) in the detection and follow up of various cervical lesions that may predispose to cervical carcinoma with special emphasis on Cervical Intraepithelial Neoplastic (CIN) conditions or dysplasias. Patients and Methods: This retrospective study M’as performed on 1500 women aged 20 years and above who attended the private clinical laboratory of the senior investigator during the period betM’een (May 2000 to May 2001). Cases were randomly selected. All relevant clinico-pathological data were recorded within a standardized interview report. After careful examination of the external genitalia, a Pap smear M’as obtained using Ayre’s wooden spatula. Results were recorded and statistically analyzed. Results: Cytological diagnosis revealed: 1065 cases (71.01%) of non specific cervicitis. 392 cases (26.13%) of specific cervicitis. 30 cases (2%) of cervical polyp. 172 cases (11.47%) of CIN! (mild dysplasia). 31 cases (2.07%) of CINj (moderate dysplasia). 10 cases (0.67%) ofCIN